1999
DOI: 10.1056/nejm199910143411606
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Treatment of Early-Stage Lung Cancer

Abstract: Our analyses suggest that the lower survival rate among black patients with early-stage, non-small-cell lung cancer, as compared with white patients, is largely explained by the lower rate of surgical treatment among blacks. Efforts to increase the rate of surgical treatment for black patients appear to be a promising way of improving survival in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
563
8
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 916 publications
(610 citation statements)
references
References 24 publications
31
563
8
4
Order By: Relevance
“…In striking contrast to studies that demonstrated an association between nonwhite race and inferior cancer care and, ultimately, unfavorable long-term survival, [14][15][16][17][18][19][20][21] we observed that nonwhite race predicted improved surgical care, as defined by adequate lymph node evaluation. Because African Americans and Hispanics tend to be uninsured and of lower socioeconomic status, it is possible that university centers are the likely providers of their surgical care: These findings are contrary to popular opinion.…”
Section: Discussioncontrasting
confidence: 99%
“…In striking contrast to studies that demonstrated an association between nonwhite race and inferior cancer care and, ultimately, unfavorable long-term survival, [14][15][16][17][18][19][20][21] we observed that nonwhite race predicted improved surgical care, as defined by adequate lymph node evaluation. Because African Americans and Hispanics tend to be uninsured and of lower socioeconomic status, it is possible that university centers are the likely providers of their surgical care: These findings are contrary to popular opinion.…”
Section: Discussioncontrasting
confidence: 99%
“…First, almost all patients in this study were Caucasian. In the USA, the patients had different ethnic backgrounds and it has been demonstrated that differences in performing preoperative staging investigations, TNM stage and use of treatment modalities were not only present for SES but also for race (Klabunde et al, 1998;Bach et al, 1999;Merrill et al, 2000;Dominitz et al, 2002;Tomar et al, 2004;Ward et al, 2004;Steyerberg et al, 2005). As a consequence, race might be a more important factor compared to SES.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated ethnic differences in survival rates of patients with lung, endometrial, and cervical carcinoma 1,6,8,[11][12][13][14][15][16] Most of these studies attribute this difference in survival rate to the greater percentage of AAs presenting at an advanced stage, having poor socioeconomic status with impediments to care. 1,6,8,[11][12][13][14] Other studies suggest an intrinsic genetic or social factor that may adversely affect cancer survival. 6,15,17 Mundt et al examined 555 patients with advanced invasive cervical carcinoma and found a decreased 8-year survival rate for AAs at 48% compared with 61% for Caucasians.…”
Section: Discussionmentioning
confidence: 99%